1979
DOI: 10.1210/endo-104-6-1667
|View full text |Cite
|
Sign up to set email alerts
|

Rat Liver Alcohol Dehydrogenase Activity: Effects of Growth Hormone and Hypophysectomy*

Abstract: Previously demonstrated increases in liver alcohol dehydrogenase in experimental uremia and after stress in the rat may be mediated by hormonal changes found in these conditions. In this study, the effects of corticosteroids, GH, adrenalectomy, and hypophysectomy on the activity of liver alcohol dehydrogenase in the rat were determined. Neither the daily administration of hydrocortisone, corticosterone, or corticotropin for 6 days nor adrenalectomy had any effect on the enzyme activity. Bovine GH, administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1983
1983
2002
2002

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Rates of cytosolic iV-hydroxyarylamine and hydroxysteroid sulf ations are also differ between the sexes (15,16,33). hepatic proteins in rats (22,23,29,30,34,35). Thus, the effect of pituitary factor on T s sulfotransferase in rat livers was examined.…”
Section: Sulfation Of T and Its Regulation By Gh And T-mentioning
confidence: 99%
“…Rates of cytosolic iV-hydroxyarylamine and hydroxysteroid sulf ations are also differ between the sexes (15,16,33). hepatic proteins in rats (22,23,29,30,34,35). Thus, the effect of pituitary factor on T s sulfotransferase in rat livers was examined.…”
Section: Sulfation Of T and Its Regulation By Gh And T-mentioning
confidence: 99%
“…Some authors have shown that estrogen increased and testosterone decreased hepatic ADH activities, whereas others have found no effect (40,41,52). Growth hormone (GH) has also been shown to be important in regulation of hepatic ADH-specific activity and transcriptional regulation of mRNA in vivo and in vitro, respectively (39,49). Sexual dimorphic expression of hepatic genes in rats is most often due to sexual difference in the GH secretory pattern, which is regulated, in part, by sex steroid hormones (20,54).…”
mentioning
confidence: 99%
“…33 In primary hepatocyte culture, continuous exposure to growth hormone, which mimics the female pattern, increases ADH message and activity, 8 and these effects are initiated at the level of transcription. 13 Hypophysectomy increases ADH activity, 39,40 and, in these rats, steady infusion of growth hormone increases ADH message and activity, whereas intermittent injection reduces the enzyme message and activity. 40 A direct effect of androgens on ADH activity, shown in this study, in hepatocyte culture may also occur in vivo.…”
Section: Discussionmentioning
confidence: 97%